Investigation of thermal conductivity enhancement of POE oil by the addition of nanoparticles - Haque, Muhammad Ehteshamul; Shakaib, M.; Rosli, A. B. (TECCIENCIA, 2024)
Metallic or non-metallic nanoparticles are dispersed in the common heat transfer fluids to create nanofluids. In this study, the KD2 Pro instrument is used to experimentally measure the thermal conductivity of Polyol Easter Oil (POE) with varying concentrations of Al2O3, TiO2, and SiO2 nanoparticles. The findings of the experiment are compared with well-established correlations for estimating the thermal conductivity of nanofluids. The measurement showed that the thermal conductivity of nanofluids increases linearly with nanoparticle concentration. The highest thermal con-ductivity was achieved by a 0.1% concentration of Al2O3 in the base fluid, which was 1.4 times more effective than POE oil as the base lubricant with thermal conductivity of 0.188 W.(mK)-1.